The Origin and Rationale of X-bar Syntax - Jacobsen, Bent (HERMES - Journal of Language and Communication in Business, 1993)
The present paper is intended as a reasonably elementary introduction to the nature of X-bar syntax, an important module in the structure of a modern transformational-generative grammar. The examples have been taken from English; however, since X-bar syntax is an integral part of the overall structure of Universal Grammar, the analyses presented here extend to any language.